MONITORING DAN CONTROLLING PADA PROSES BUNKERING DI KAPAL BERBASIS INTERNET OF THINGS - Djumingan, Sartono; Siswanto , Diky; Subhan, Muh Uhida (Program Studi Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2024)
Bunkering or refueling a ship is a routine activity for a ship before sailing. Before refueling, the ship must prepare safe, efficient, and controlled bunkering procedures. Ships that are bunkering or refueling while anchored or docked can cause pollution at sea. This oil spill results in pollution due to tanker operations. The impact of the oil spill still needs to be resolved, as the oil spill will merge into the cells of marine living creatures such as fish, shrimp, and squid. If it is not addressed for longer, it will damage the food chain around the sea and be consumed by humans. This paper presents research on monitoring and controlling the bunkering process in a ship utilizing the Internet of Things. A prototype system was proposed to monitor the level of fuel entering the ship and be able to turn off the fuel oil pump when it reaches the threshold so that it does not spill into the sea. When the pump stops, an alarm will sound to provide a warning. The ultrasonic sensor is used to detect fuel levels. Based on the research results, it has a deviation value of 0.275 cm. The observed liquid height level monitoring data can be viewed directly from the smartphone.